Spanish use in the English classroom: a study of Dominican students in an English-only environment - Diaz, Alexander Lopez (Beyond Words, 2019)
The native language use in the target language classroom has recently gained the attention of second language acquisition research. This study analyzes such issue in the context of Dominican university students, ranging from 18 to 35 years old, studying in an English immersion program, who have been speaking their native language, namely, Spanish too often in their classrooms. This research focuses on identifying the causes for students to use their native language in the class, and their attitude towards both, Spanish and English, by implementing a survey to 37 of these students. To better understand the problem and create potential strategies to address it, firstly, literature has been visited by presenting relevant research related to second language learning and acquisition. Secondly, the methodology is explained so that the research context can be more readily understood. Subsequently, results from surveys are analyzed in the light of current second language acquisition research. As a conclusion, this study revealed that students use their native language primarily when prompted by their partners, when in need of clarification, when unable to understand a concept, and overwhelmingly as a means to making oneself clear. The teaching implications of these findings are also discussed in the end.